Image differentiation for competitive advantage in the private tertiary education institutions in Botswana - Douglas Chiguvi; Ruramayi Tadu (Dutch Journal of Finance and Management, 2020)
The primary objective of the study was to describe the extent to which image differentiation strategies may be used to gain competitive advantage among private tertiary education institutions in Botswana. The study examined how image differentiation may be employed by private tertiary education institutions to achieve competitive advantage. The study used descriptive survey research and the findings revealed that the institutions have not done enough in image differentiation to clearly stand out as differentiated universities. The study recommends that the universities must get involved in activities that will enhance institutions' image. Institutions need to work together with key stakeholders and continually seek ways to attain competitive advantage through image differentiation.
Keywords: 650; image differentiation; competitive advantage; private tertiary institutions